Reed Warbler Hosts Do Not Fine-Tune Mobbing Defenses During the Breeding Season, Even When Cuckoos Are Rare - Tolman, Deryk; Campobello, Daniela; Rönkä, Katja; Kluen, Edward; Thorogood, Rose (Frontiers in Ecology and Evolution, 2021)
Hosts of brood parasitic cuckoos often employ mobbing attacks to defend their nests and, when mobbing is costly, hosts are predicted to adjust their mobbing to match parasitism risk. While evidence exists for fine-tuned plasticity, it remains unclear why mobbing does not track larger seasonal changes in parasitism risk. Here we test a possible explanation from parental investment theory: parents should defend their current brood more intensively as the opportunity to replace it declines (‘re-nesting potential’), and therefore ‘counteract’ any apparent seasonal decline to match parasitism risk. We take advantage of mobbing experiments conducted at two sites where reed warblers (Acrocephalus scirpaceus) experience (in Italy), or do not experience (in Finland), brood parasitism. We predicted that mobbing of cuckoos should be higher overall in Italy, but remain constant over the season as in other parasitised sites, whereas in Finland where cuckoos do not pose a local threat, we predicted that mobbing should be low at the beginning of the season but increase as re-nesting potential declined. However, while cuckoos were more likely to be mobbed in Italy, we found little evidence that mobbing changed over the season at either the parasitized or non-parasitized sites. This suggests that re-nesting potential has little influence on mobbing behaviour, or that its effects are obscured by other seasonal differences in ecology or experience of hosts.